Comment on "Acetylcysteine in paracetamol poisoning: a perspective of 45 years of use" by D. N. Bateman and J. W. Dear, Toxicol. Res., 2019, 8, 489. Issue 6 (3rd October 2019) - Mullins, Michael E.; Yarema, Mark C.; Sivilotti, Marco L. A.; Thompson, Margaret; Algren, D. Adam; Beuhler, Michael C.; Holstege, Christopher P.
Abstract : We point out an acetylcysteine protocol that a previous article (D. N. Bateman and J. W. Dear, Toxicol. Res., 2019, 8, 489–498) overlooked. Abstract: We point out an acetylcysteine protocol that a previous article (D. N. Bateman and J. W. Dear, Toxicol. Res., 2019, 8, 489–498) overlooked. The standard concentration protocol uses a uniform concentration of 30 mg mL −1 for all patients to reduce errors in preparation and administration. Usually a single 1 L bag is sufficient for most patients. Various centers in the US and Canada use this approach.